Intrinsic brain activity differences in drug-resistant epilepsy and well-controlled epilepsy patients: an EEG microstate analysis - Chaofeng Zhu; Jinying Zhang; Shenzhi Fang; Yuying Zhang; Juan Li; Luyan Wu; Huapin Huang; Wanhui Lin (Therapeutic Advances in Neurological Disorders)
Background: Drug-resistant epilepsy (DRE) patients exhibit aberrant large-scale brain networks. Objective: The purpose of investigation is to explore the differences in resting-state electroencephalogram (EEG) microstates between patients with DRE and well-controlled (W-C) epilepsy. Design: Retrospective study. Methods: Clinical data of epilepsy patients treated at the Epilepsy Center of Fujian Medical University Union Hospital from January 2020 to May 2023 were collected for a minimum follow-up period of 2 years. Participants meeting inclusion and exclusion criteria were categorized into two groups based on follow-up records: W-C group and DRE group. To ensure that the recorded EEG data were not influenced by medication, all EEG recordings were collected before patients commenced any antiepileptic drug treatment. Resting-state EEG datasets of all participants underwent microstate analysis. This study comprehensively compared the average duration, frequency per second, coverage, and transition probabilities (TPs) of each microstate between the two groups. Results: A total of 289 individuals who met the criteria were included, categorized into the W-C group ( n  = 112) and the DRE group ( n  = 177). EEG microstate analysis revealed substantial variances between the two groups. The analysis highlights differences in three of four microstate classifications. Microstate transition analysis demonstrated altered probabilities in DRE patients. Increased probabilities were observed in TP AB , TP BA , TP BC , TP CB , TP BD , and TP DB . Decreased probabilities included TP CA , TP DA , TP AC , TP AD , TP CD , and TP DC . Conclusion: This study highlights distinctive EEG microstate parameters and TPs in DRE patients compared to those with W-C epilepsy. The results may potentially advance the clinical application of EEG microstates.